Análises, aplicações e validações–numérico/experimentais do modelo SWAN em áreas restritas e ao largo - Vieira, Adriana Silveira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research deals with the monitoring and the forecasting of wind wave generation and propagation at Praia da Vitória – Azores - Portugal and at the reservoir of Ilha Solteira Dam – São Paulo – Brazil. The SWAN numerical model (Simulating Waves Nearshore) is employed. Such a model is able to simulate the generation, propagation and dissipation of sea waves, based on the equation for wave action conservation. In the sea-wave propagation across both open and confined coastal regions, the model simulates the physical processes of refraction, diffraction and shoaling due to bottom depth variations. It also is capable of simulate the presence of currents, as well as wave growth due to wind, bottom induced wave breaking and whitecapping, energy dissipation due to bottom friction, wave blocking and reflection by currents and wave transmission across obstacles. Among the several results produced by SWAN model, it is worth mentioning significant wave height, mean and peak periods, mean and peak directions, directional spreading, bandwidth parameter and sea level anywhere in the computational domain. Two applications of SWAN model are developed to simulate sea-wave generation and propagation at two distinct locations: one corresponds to an open coast location – the maritime region adjacent to Praia da Vitória port, on Terceira Island, Azores archipelago, Portugal; and the other corresponding to a confined region, the reservoir of Ilha Solteira Dam, São Paulo, Brazil. For Praia da Vitória port, results from offshore sea wave forecasts obtained through the large scale model WAVEWATCH III and wind data from MM5 model were used as forcing data for SWAN model. The numerical results were compared to sea-wave data obtained from a wave buoy deployed 4 km away from the coast at water depth of 90 m (Point 2), during 2009 and 2010 with three-hourly averages. The numerical model SWAN proved itself quite ...

Esta pesquisa trata do monitoramento e da previsão da geração de agitação pela ação do vento e da propagação de estados de agitação em dois locais: Porto da Praia da Vitória – Açores – Portugal e Lago da Barragem de Ilha Solteira – São Paulo – Brasil. A metodologia abordada utiliza o modelo numérico SWAN (Simulating WAves Nearshore) que é capaz de simular a geração, propagação e dissipação da agitação marítima, com base na equação para a conservação da ação de onda. Na propagação da agitação marítima, em zonas costeiras abertas ou confinadas, o modelo simula os processos físicos de refração, difração e empolamento devido a variações do fundo e presença de correntes. Também integra na simulação o crescimento de onda por ação dos ventos, a arrebentação por influência do fundo e por excesso de declividade (whitecapping), a dissipação de energia por causa de fricção do fundo, o bloqueio e reflexão por correntes opostas, e a transmissão através de obstáculos. Entre os vários resultados obtidos através do SWAN, destacam-se a altura significativa, os períodos de pico e médio, as direções de pico e média, a dispersão direcional, o parâmetro de largura de banda e nível de água em qualquer parte do domínio computacional. Duas aplicações do modelo SWAN são tratadas nesta tese para a simulação da geração e da propagação de ondas em dois locais distintos: um correspondente a uma zona costeira aberta – a zona marítima adjacente ao porto da Praia da Vitória, na Ilha Terceira do Arquipélago dos Açores, Portugal; e outro correspondente a uma zona confinada, o lago da barragem de Ilha Solteira, São Paulo, Brasil. Para o Porto da Praia da Vitória, utilizaram-se os resultados das previsões da agitação marítima ao largo da zona em estudo, obtidos com o modelo de previsão de larga escala WAVEWATCH III e os dados de vento do ...
Keywords: Ondas gravitacionais; Ondas produzidas pelo vento; Ventos; Lagos; Wind waves